Kesiapan Masyarakat Lokal dalam Pengembangan Desa Carangsari sebagai Desa Wisata di Kabupaten Badung - Julia, Reinda Chella; Mertha, I Wayan; Susianti, Woro (Journal of Tourism and Creativity, 2024)
This study aims to determine the level of readiness of the local community in the development of Carangsari Village as a tourist village in Badung Regency, using quantitative and qualitative approaches. Data collection used survey techniques, interviews, and documentation. A total of 98 respondents were obtained using purposive accidental sampling technique, and the determination of informants was carried out using snowball sampling technique, by first determining key informants. Data were analyzed descriptively using the community readiness model. The results showed that the readiness level of Carangsari Village scored 7.8 and was at the preparation stage. This means that the local community of Carangsari Village is still in the preparation stage to carry out efforts to develop a tourist village, with leadership characteristics and the availability of information in Carangsari Village already classified as good. However, community involvement and cooperation with other stakeholders still cannot improve community readiness in the development of tourism villages. The dimension of readiness that has the highest score of 9.4 is leadership, while the dimension with the lowest score of 5.4 is community efforts.